Le règne de la scientificité: histoire de l'étiologie des maladies infectieuses dans la presse médicale du Québec, 1840-1880 - Beaudry, Louka (Université de Montréal, 2013)
Keywords: Médecine

Artisans et ouvriers à l’époque des revendications démocratiques et nationalitaires du Parti patriote dans le Bas-Canada, 1832-1838: un rendez-vous manqué avec l’histoire ? - Tremblay, Robert (Bulletin d'histoire politique, 2017)
Keywords: Partis politiques; Tracey, Daniel; Élections

La petite histoire, des origines jusqu'à 1925. Des carrières sous le parc Laurier - Côté, Julie; Cudia, Caroline (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
Keywords: Carrière; Parcs; Travail

Une forme d'entraide populaire: histoire des sociétés québécoises de secours mutuels au 19e siècle - Petitclerc, Martin (Université du Québec à Montréal, 2004)
Keywords: Assurance; Banques; Pauvreté; Union Saint-Joseph

Carrières et pierre grise (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
Keywords: Carrière; De Lorimier (village); Géographie physique; Géologie; Histoire naturelle; Parcs; Plateau Mont-Royal; Quartiers; Travail; Villages; Églises

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Histoire sociale / Social History, 1984)
Keywords: Famille; Femmes; Travail

Le syndicalisme québécois: deux siècles d'histoire - Rouillard, Jacques (Boréal, 2004)
Keywords: Confédération des syndicats nationaux; Confédération des travailleurs catholiques du Canada (C.T.C.C.); Fédération des travailleurs et travailleuses du Québec (FTQ); Grèves; Travail

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Chemins de fer; Musique; Noirs; Travail

L'histoire des cols bleus regroupés de Montréal. Tome 1: De ses origines à 1963 - Lapierre, Jean (2008)
Keywords: Travail

La grève des charretiers à Montréal, 1864 - Heap, Margaret (Revue d'histoire de l'Amérique française, 1977)
Keywords: Charretiers; Grèves

La formation matérielle de la classe ouvrière à Montréal entre 1790 et 1830 - Tremblay, Robert (Revue d'histoire de l'Amérique française, 1979)
Keywords: Artisans

L'industrie de la chaussure à Montréal: 1840-1870 - Le passage de l'artisanat à la fabrique - Burgess, Joanne (Revue d'histoire de l'Amérique française, 1977)
Keywords: Artisans; Chaussure

Des Forges du Saint-Maurice aux fonderies de Montréal: mobilité géographique, solidarité communautaire et action syndicale des mouleurs, 1829-1881 - Bischoff, Peter (Revue d'histoire de l'Amérique française, 1989)
Keywords: Artisans; Famille; Fer et acier; Mouleurs

Population, identités sociales et vie quotidienne - Gauvreau, Danielle (Histoire de Montréal et de sa région, 2012)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Le travail et la classe ouvrière montréalaise au XIXe siècle - Petitclerc, Martin (Histoire de Montréal et de sa région, 2012)
Keywords: Chevaliers du Travail; Conseil des métiers et du travail de Montréal; Grande Association; Grèves; Pauvreté; Syndicats internationaux; Travail

Class, Gender and the Law in Eighteenth and Nineteenth Century Quebec: Sources and Perspectives - Fyson, Donald; M. Coates, Colin; Harvey, Kathryn (Occasional Papers of the Montreal History Group, 1993)
Keywords: Criminalité; Mariage; Police; Prostitution; Travail; Tribunaux

Wage Disputes and the Courts in Montreal, 1816-1835 - Laing Hogg, Grace; Shulman, Gwen (Class, Gender and the Law in Eighteenth and Nineteenth Century Quebec: Sources and Perspectives, 1993)
Keywords: Travail; Tribunaux

L'industrie de la chaussure à Montréal 1840-1870: de l'artisanat à la fabrique - Burgess, Joanne (Université du Québec à Montréal, 1977)
Keywords: Artisans; Chaussure

Les ouvriers mouleurs à Montréal, 1859-1881 - Bischoff, Peter (Université du Québec à Montréal, 1986)
Keywords: Fer et acier; Mouleurs

La nature des procès de travail à Montréal entre 1790 et 1830 - Tremblay, Robert (Université de Montréal, 1979)
Keywords: Artisans

The Legal Rights of Masters, Mistresses and Domestic Servants in Montreal, 1816-1829 - Hogg, Grace Laing (Université McGill, 1989)
Keywords: Domestiques; Femmes

Apprenticeship in Early Nineteenth Century Montreal, 1790-1812 - Audet, Pierre-H. (Université Concordia, 1975)
Keywords: Apprentissage; Travail

The Size of the Labour Force in the Montreal Fur Trade, 1675-1790: A Critical Evaluation - Murphy, Brian D. (Université d'Ottawa, 1986)
Keywords: Engagés; Fourrure

Tensions et solidarité: la formation des traditions syndicales chez les mouleurs de Montréal, Hamilton et Toronto, 1851 à 1893 - Bischoff, Peter (Université de Montréal, 1992)
Keywords: Fer et acier; Mouleurs

Aspects démographiques de la vie des couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Cahiers d'histoire, 2010)
Keywords: Confection; Femmes

Des emplois pour une élite cultivée: travailler pour l’Assemblée législative de la province du Canada, 1840-1850 - Roy, Alain (Bulletin d'histoire politique, 2017)
Keywords: Fonctionnaires; Parlement

Main-d'oeuvre immigrante et développement dualiste: l'économie canadienne au milieu du XIXe siècle - Seccareccia, Mario; Saint-Germain, Maurice (Histoire sociale / Social History, 2001)
Keywords: Britanniques

En rade: marins à Montréal (1851-1896) - Bélisle-Desmeules, David (Domaine histoire, 2019)
Keywords: Navigation; Port; Travail; Vieux-port

L’émeute de Lachine en 1812: la coordination d’une contestation populaire - Dessureault, Christian (Revue d'histoire de l'Amérique française, 2008)
Keywords: Lachine; Émeutes

Solemn Processions and Terrifying Violence: Spectacle, Authority, and Citizenship during the Lachine Canal Strike of 1843 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2010)
Keywords: Grèves; Irlandais; Lachine (canal)

À chacune son rang. Les ''filles données'' des Soeurs Grises 1855-1905 - Gervais, Diane (Revue d'histoire de l'Amérique française, 2014)
Keywords: Communautés religieuses; Domestiques; Femmes; Soeurs Grises

Note de recherche. Les journaliers dans le district de Montréal en 1831 - Dessureault, Christian (Revue d'histoire de l'Amérique française, 2021)
Keywords: Famille; Recensements; Travail

Tanneurs et tanneries dans le gouvernement de Montréal au XVIIIe siècle - Perrier, Jocelyne (Université de Montréal, 2002)
Keywords: Artisans; Tannerie

Aspects sociaux et économiques du veuvage à Montréal au milieu du 19e siècle - Favel, Valentine (Université Lumière Lyon 2, 1991)
Keywords: Famille; Femmes; Veuvage

Du forgeron au machiniste: l'impact social de la mécanisation des opérations d'usinage dans l'industrie de la métallurgie à Montréal de 1815 à 1860 - Tremblay, Robert (Université du Québec à Montréal, 1992)

Les jardiniers professionnels de Montréal au XVIIIe siècle - Fortin, Guillaume (Université du Québec à Montréal, 2019)
Keywords: Jardins; Travail

Tensions et solidarité: la formation des traditions syndicales chez les mouleurs de Montréal, Hamilton et Toronto, 1851 à 1893 - Bischoff, Peter (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1992)
Keywords: Fer et acier; Mouleurs

Les pionniers du mouvement ouvrier au Québec: quelques pistes de réflexion sur la première génération de militants des années 1830 - Tremblay, Robert (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2012)
Keywords: Charpentiers; Chaussure; Confection; Imprimerie; Menuisiers

Montréal, 1840-1870: le passage de l'artisanat à la fabrique - Burgess, Joanne (Les métiers du cuir, 1981)
Keywords: Artisans; Chaussure

The Segregated City: Class and Occupation in Montreal 1861-1901/La ville différenciée: professions et classes sociales à Montréal, 1861-1901 - Lewis, Robert D. (Université McGill, Département de géographie, 1985)
Keywords: Locataires; Logement; Mobilité résidentielle

The Segregated City: Residential Differentiation, Rent and Income in Montreal, 1861-1901 - Lewis, Robert D. (Université McGill, 1985)
Keywords: Locataires; Logement; Mobilité résidentielle

Women and Wage Labour in a Period of Transition, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1987)
Keywords: Famille; Femmes; Travail

Some Early Teachers' Associations in Quebec - Cooper, John Irwin (Educational Record of the Province of Quebec, 1964)
Keywords: Enseignants; Hicks, William Henry; Lower Canada Teachers' Association

Souvenirs sur les commencements de l'Union St-Joseph de Montréal - Plinguet, J. A. (Plinguet et Laplante, 1866)
Keywords: Assurance; Union Saint-Joseph

Les domestiques en milieu urbain au début du XIXe siècle - Lacelle, Claudette (Parcs Canada, 1980)
Keywords: Domestiques; Femmes

La grève des charretiers à Montréal, 1864 - Heap, Margaret (Le mouvement ouvrier au Québec, 1980)
Keywords: Charretiers; Grèves

The Growth of a Craft Labour Force: Montréal Leather Artisans, 1815-1831 - Burgess, Joanne (CHA / SHC, Historical Papers / Communications historiques, 1988)
Keywords: Artisans; Chaussure; Sellerie; Tannerie

Dimensions of Paternalism: Discipline and Culture in Canadian Railway Operations in the 1850s - Craven, Paul; Traves, Tom (On the Job: Confronting the Labour Process in Canada, 1986)
Keywords: Chemins de fer; Grand Tronc

The Lachine Strike of 1843 - Pentland, H. C. (Canadian Historical Review, 1948)
Keywords: Grèves; Irlandais; Lachine (canal)

La formation des traditions de solidarité ouvrière chez les mouleurs montréalais: la longue marche vers le syndicalisme (1859-1881) - Bischoff, Peter (Labour / Le travailleur, 1988)
Keywords: Fer et acier; Mouleurs

Early Trade Unionism in Quebec - 1833-1834: the Carpenters' and Joiners' General Strike in Montreal - Vance, C. (The Marxist Quarterly, 1962)
Keywords: Charpentiers; Grèves; Menuisiers

"Traveling the Country 'round": migrations et syndicalisme chez les mouleurs de l'Ontario et du Québec membres de l'Iron Molders Union of North America, 1860 à 1892 - Bischoff, Peter (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1990)
Keywords: Fer et acier; Iron Molders Union of North America; Mouleurs

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Taking to the Streets: Crowds, Politics, and the Urban Experience in Mid-Nineteenth-Century Montreal - Horner, Dan (Études d'histoire du Québec / Studies on the history of Quebec, 2020)
Keywords: Grèves; Incendies; Lachine (canal); Parlement; Rues; Rébellions; Réformistes; Émeutes